Transformation of Payment in Education Use Bitcoin with Reduced Confirmation Times - Henderi; Aini, Qurotul; Manongga, Danny; Sembiring, Irwan; Apriliasari, Dwi (Pandawan, 2023)
Significant changes in the financial system are prompted by the growth of the national economy, particularly as a form of payment. The means evolved from barter to things or commodities to metal and paper as the base materials for money before arriving at barter. With such significant changes, there is also a need for a transformation in the world of education in order to welcome technological advancements and one way to survive the changes in the increasingly rapid digital era. As the economic need increases, trade transaction methods shift from traditional to internet-based. One of the necessary international online payment options is bitcoin. For many applications where payments are modest and instantaneous approval is required, Bitcoin is inappropriate because of the high transaction fees and long confirmation periods. As a result, despite the introduction of numerous rival cryptocurrencies to address these problems, the Bitcoin network continues to be the most extensively used payment method. Unquestionably, new finding of this research that effectively address the problems of high transaction costs and transaction verification times are needed if the company is to benefit from its user network. The Lightning Network (LN), which makes use of off-chain bidirectional payment channels between participants, is one of the most recent payment network concepts to be proposed.